Outcomes of Patients Undergoing Renal Replacement Therapy in ICU in a Tertiary Level Teaching Hospital in Nepal- A Registry Based Retrospective Study. - Karki, Bipin; Pradhan, Utsav Lal; Baral, Pankaj; Timasina, Ravi; Acharya, Subhash Prasad; Shrestha, Gentle Sunder (Journal of Nepalese Society of Critical Care Medicine, 2026)
Background and aims: Requirement of renal replacement therapy (RRT) is associated with adverse clinical outcomes in intensive care unit (ICU). However, most of the studies have not included data from low- and middle- income countries (LMICs). This study aims to compare the characteristic and outcomes of patients undergoing RRT with those not requiring RRT (NRRT) in ICU. Methods: This is a registry based retrospective cohort study of patients requiring RRT in a tertiary level university hospital in Nepal. We compared patients requiring RRT with those not requiring RRT for outcomes including ICU mortality, Length of stay in ICU (LOS-ICU) and duration of mechanical ventilation (MV). Odds ratio (OR) was calculated for between group comparison.Results: Of the 3,733 patients admitted during the period of 3 years (January 1, 2020 to December 31, 2022), 516 (13.82%) underwent RRT. When compared with NRRT group, acute physiology and chronic health evaluation (APACHE) II scores, requirement of MV and non-invasive ventilation (NIV) were higher in RRT group. Also, RRT group had higher ICU mortality (OR 3.00, 95% CI 2.42-3.70, p